Dual-targeting CRISPR-CasRx reduces C9orf72 ALS/FTD sense and antisense repeat RNAs in vitro and in vivo - Liam Kempthorne; Deniz Vaizoglu; Alexander J. Cammack; Mireia Carcolé; Martha J. Roberts; Alla Mikheenko; Alessia Fisher; Pacharaporn Suklai; Bhavana Muralidharan; François Kroll; Thomas G. Moens; Lidia Yshii; et al. (Nature Communications)
Abstract The most common genetic cause of frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) is an intronic G4C2 repeat expansion in C9orf72. The repeats undergo bidirectional transcription to produce sense and antisense repeat RNA species, which are translated into dipeptide repeat proteins (DPRs). As toxicity has been associated with both sense and antisense repeat-derived RNA and DPRs, targeting both strands may provide the most effective therapeutic strategy. CRISPR-Cas13 systems mature their own guide arrays, allowing targeting of multiple RNA species from a single construct. We show CRISPR-Cas13d variant CasRx effectively reduces overexpressed C9orf72 sense and antisense repeat transcripts and DPRs in HEK cells. In C9orf72 patient-derived iPSC-neuron lines, CRISPR-CasRx reduces endogenous sense and antisense repeat RNAs and DPRs and protects against glutamate-induced excitotoxicity. AAV delivery of CRISPR-CasRx to two distinct C9orf72 repeat mouse models significantly reduced both sense and antisense repeat-containing transcripts. This highlights the potential of RNA-targeting CRISPR systems as therapeutics for C9orf72 ALS/FTD.